The immediate effects of exercise using the Functional Re-adaptive Exercise Device on lumbopelvic kinematics in people with and without low back pain. (January 2017) - Winnard, A.; Debuse, D.; Wilkinson, M.; Tahmosybayat, R.; Caplan, N.
Abstract: Background: Dysfunction of the lumbar multifidus (LM) and transversus abdominis (TrA) muscles is associated with low back pain (LBP). The Functional Re-adaptive Exercise Device (FRED) has shown potential as a non-specific LBP intervention by automatically recruiting LM and TrA. Loss or lordosis and altered lumbopelvic positioning has also been linked to LBP and is often trained within LM and TrA interventions. The effect that FRED exercise has on lumbopelvic positioning and lumbar lordosis is unknown. Objectives: To assess the effect of FRED exercise on lumbopelvic kinematics and alignment to establish whether FRED exercise promotes a favourable lumbopelvic posture for training LM and TrA. Design: Within and between-group comparison study. Method: One hundred and thirty participants, 74 experiencing LBP, had lumbopelvic kinematic data measured during over-ground walking and FRED exercise. Magnitude-based inferences were used to compare walking with FRED exercise within participants and between the asymptomatic and LBP groups, to establish the effects of FRED exercise on lumbopelvic kinematics, compared to walking, in each group. Results: FRED exercise promotes an immediate change in anterior pelvic tilt by 8.7° compared to walking in the no-LBP and LBP groups. Sagittal-plane spinal extension increased during FRED exercise at all spinal levels by 0.9° in the no-LBP group, and by 1.2° in the LBP group. Conclusions: FRED exercise promotes a lumbopelvic position more conducive to LM and TrA training than walking in both asymptomatic people and those with LBP. Highlights: A posture conducive to LM and TrA training was promoted. The posture appears to occur automatically in people with and without LBP. Exercise on the FRED may be effective for LM and TrA training.